Evanescent waveguide mode induced surface plasmonic wave excitation in subwavelength hole array enhanced quantum dot infrared photodetectors. (31st May 2018) - Gu, Guiru; Vasinajindakaw, Puminun; Zhang, Yingjie; Kemsri, Thitikorn; Li, Lin; Xiang, Boyang; GhafaryAghdam, Ainaz; Lu, Xuejun
Abstract: In this paper, we present the analysis of the evanescent waveguide modes in a 2D subwavelength hole array (2DSHA) plasmonic structure and their relationship with the excited surface plasmonic resonance (SPR). It is found that when the metal film thickness is larger than 0.0625 µ m, the excited SPRs have a linear dependence on the evanescent waveguide modes, whereas when the metal film is thin, the linear relationship does not hold, primarily due to the coupling of the SPRs on the asymmetric interfaces of the metal film. The linear dependence is also verified by curve-fitting the Fano transmission profiles of the 2DSHA structures. 2DSHA enhanced quantum dot infrared photodetectors with various metal film thicknesses were fabricated and tested. The measured plasmonic enhancement ratios agree well with the analysis.